Missauri Mathematics Project Berbasis Soal Open Ended terhadap Kemampuan Komunikasi Matematika - Idul Adha; Rani Refianti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this study was to determine the effect of the missauri mathematic project model based on open ended questions on students' mathematical communication skills. The population of this study was all VII grade students of SMP Negeri 8 Lubuklinggau in the 2018/2019 academic year while the samples in this study were taken randomly. Data collection techniques using test techniques consisting of a description test conducted twice, namely the initial ability test to see mathematical communication skills before participating in learning and the final ability test after following learning. The data analysis techniques of this study are the normality test, homogeneity test and t-test. Based on the results of the t-test analysis with a significance level α = 0.05, obtained tcount> ttable (6.92> 1.67), so it can be concluded that there is an influence of missauri mathematical project learning model based on open ended questions on the mathematical communication skills of class students VII SMP N 8 Lubuklinggau. Keywords: Communication Skills, Mathematical Project Missauri, Opend Ended